2012
DOI: 10.1104/pp.111.191072
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Methylthioadenosine Is Essential for Normal Vascular Development and Reproduction in Arabidopsis    

Abstract: 5#-Methylthioadenosine (MTA) is the common by-product of polyamine (PA), nicotianamine (NA), and ethylene biosynthesis in Arabidopsis (Arabidopsis thaliana). The methylthiol moiety of MTA is salvaged by 5#-methylthioadenosine nucleosidase (MTN) in a reaction producing methylthioribose (MTR) and adenine. The MTN double mutant, mtn1-1mtn2-1, retains approximately 14% of the MTN enzyme activity present in the wild type and displays a pleiotropic phenotype that includes altered vasculature and impaired fertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
(84 reference statements)
1
27
1
Order By: Relevance
“…S5 and S6). This is in contrast to the results of Waduwara-Jayabahu et al (2012), in which the addition of spermidine had the strongest positive effect. While the mtn1/mtn2 double knockout plants accumulated MTA, which caused feedback inhibition of PA synthases and ultimately lead to thermospermine deficiency with thermospermine-dependent vascular defects, the mti1 and dep1 mutants rather suffered from a lack of spermine and displayed stress-related phenotypes.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…S5 and S6). This is in contrast to the results of Waduwara-Jayabahu et al (2012), in which the addition of spermidine had the strongest positive effect. While the mtn1/mtn2 double knockout plants accumulated MTA, which caused feedback inhibition of PA synthases and ultimately lead to thermospermine deficiency with thermospermine-dependent vascular defects, the mti1 and dep1 mutants rather suffered from a lack of spermine and displayed stress-related phenotypes.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies showed that the Met Cycle plays an essential role for the biosynthesis of ethylene, NA, and PAs Rzewuski et al, 2007;Waduwara-Jayabahu et al, 2012) and that in Arabidopsis the enzymes MTI1 and DEP1 were able to complement yeast mutants defective in the Met Cycle (Pommerrenig et al, 2011). So far, a characterization of the functional importance of the two enzymes in planta and their involvement in any of the Met Cycledependent pathways was lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps certain Yang cycle metabolites are being translocated between the pericarp tissue and vascular cells for further processing. Recently, it was shown in the Arabidopsis double mtn/ mtk mutant that efficient recycling of MTA by the Yang cycle is essential for vascular tissue development (Waduwara-Jayabahu et al, 2012).…”
Section: The Yang Cycle Genes Are Coordinately Expressed and Show A Dmentioning
confidence: 99%
“…However, we did use this output as a tool to determine whether our complementation lines contain a functional copy of MTN1. It was previously demonstrated that UBQ promoter-driven MTN1 can complement the mtn1 mtn2 reproductive and morphological defects (74). We generated T1 complementation lines and compared their developmental phenotypes with those of Col-0 and mtn1 mtn2 plants (Fig.…”
Section: Mutation Of Two Conserved Mtn Asparagine Residues To Deamidamentioning
confidence: 99%